Design And Analysis of CFD Geometry Configuration Canted Winglet Toward Aerodynamic Characteristic on Wing Profil of The UAV LSU-05 - NURUL ANWAR; Lazuardy Rahendra Pinandhita; Bangga Dirgantara Adiputra (Institut Teknologi Dirgantara Adisutjipto, 2021)
The wing is part of an aircraft or UAV which has a function as a major component of producing lift, therefore if a problem occurs such as a vortex at the end of the wing it will affect its performance capability. This study aims to determine the condition of the airflow, the value of induced drag, and the selection of the design of the wingtip devices on the wing profile of the UAV LSU-05. The method used is numerical or computational methods with CFD-based software to predict the aerodynamic characteristics and phenomenon of airflow around the wing with wingtip devices and without it. The model used in this study is a half-wing LSU-05 with NACA 4415 made with CATIA V5R20 software and the simulation uses ANSYS CFX 17.1. Based on the previous simulation results, it was found that the application of the canted winglet geometry to the wing profile of the UAV LSU-05 affects the coefficient lift (CL)/coefficient drag (CD) value and induced drag. Whereas the coefficient lift (CL)/coefficient drag (CD) value before using the canted winglet was 18.904 after application, increased to 21.616, this causes the induced drag value to change inversely with the coefficient lift (CL)/coefficient drag (CD) value where the value before the application was 30.4181 N to 29.0566 N.Keywords: Canted Winglet, CFD, Wing